2015
DOI: 10.1088/0004-637x/813/2/117
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation Activity in Clash Brightest Cluster Galaxies

Abstract: The CLASH X-ray selected sample of 20 galaxy clusters contains ten brightest cluster galaxies (BCGs) that exhibit significant (>5 σ) extinction-corrected star formation rates (SFRs). Star formation activity is inferred from photometric estimates of UV and Hα+[N II] emission in knots and filaments detected in CLASH HST ACS and WFC3 observations. UV-derived SFRs in these BCGs span two orders of magnitude, including two with a SFR 100 M yr −1 . These measurements are supplemented with [O II], [O III], and Hβ flux… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
96
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(113 citation statements)
references
References 85 publications
15
96
2
Order By: Relevance
“…In Fogarty et al (2015), we attempted to estimate the cooling rate of the ICM by measuringṀ g for gas that was at a radius < 35 kpc or for gas that had an average t cool /t f f ratio below 70 5 . We found that while reddening-corrected UV photometric SFRs scale withṀ g in both cases, star formation appears to be increasingly 'inefficient' as the SFR decreases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Fogarty et al (2015), we attempted to estimate the cooling rate of the ICM by measuringṀ g for gas that was at a radius < 35 kpc or for gas that had an average t cool /t f f ratio below 70 5 . We found that while reddening-corrected UV photometric SFRs scale withṀ g in both cases, star formation appears to be increasingly 'inefficient' as the SFR decreases.…”
Section: Discussionmentioning
confidence: 99%
“…In Fogarty et al (2015), we identified 11 BCGs in the CLASH X-ray selected sample with evidence of ongoing star formation. In each of these BCGs, we detected extended UV emission in WFC3/UVIS photometry and extended Hα + [N II] emission by differencing ACS images.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of feeding the AGN with cold clumps in the feedback mechanism cycle is termed the cold feedback mechanism, and was suggested by Pizzolato & Soker (2005). The cold feedback mechanism has been later strengthened by observations of cold gas and by more detailed studies (e.g., Revaz et al 2008;Pope 2009;Pizzolato & Soker 2010;Edge et al 2010;Wilman et al 2011;Nesvadba et al 2011;Cavagnolo et al 2011;Gaspari et al 2012a,b;McCourt et al 2012;Sharma et al 2012;Farage et al 2012;Wagh et al 2014;Banerjee & Sharma 2014;McNamara et al 2014;Li et al 2015;Prasad et al 2015;Russell et al 2015;Tremblay et al 2015;Fogarty et al 2015). Gilkis & Soker (2012) and Hillel & Soker (2014) have shown that the mixing of the hot bubble gas with the ICM is a much more efficient heating process than heating by repeated shocks; hereafter termed shocksheating.…”
Section: Introductionmentioning
confidence: 99%